Learn Python 3 from scratch (Packt Publishing, 2018)
"This is the most comprehensive yet simple course on the Python programming language and it concentrates on Python 3.x. This means that what you will learn is relevant, not obsolete. No prior coding experience is needed. Python is one of the most useful programming languages to learn. You can use it for the back-end of web applications, games, in-house scripts, and even for building robust test automation frameworks. Each lecture consist of a video screencast and code files; there are quizzes and homework to test your knowledge; there's a high focus on practice and asking questions; and you will also learn coding best practices"--Resource description page